Analisis Rasio Rentabilitas Untuk Meninjau Kinerja Keuangan Pada Perbankan Syariah dan Perbankan Konvensional Masa Pandemi Covid 19 - Toni Hidayat; Ratna Sari Dewi; Anggia Sari Lubis (Departement of Mathematics Education, 2023)
Bank performance is a very important and significant picture for the parties with an interest in the bank. The parties with an interest in the bank include investors, creditors, customers, employees, government and the surrounding community. Given the large number of interested parties, the assessment of bank performance is very important. Bank performance is assessed based on how company management carries out all of its duties. Bank health is one of the factors that must be considered by both conventional and sharia banks in order to survive. This paper aims to compare the financial performance of Islamic banking with conventional banking in the third quarter of 2020 during the Covid 19 pandemic using the ROA financial ratio.